Views by Ronald Langacker on Cognitive Semantics as a Model for Translation Quality Assessment - Shmiher, Taras (East European Journal of Psycholinguistics, 2016)
The aim of this study is to analyse the applicability of R. Langacker’s views on cognitive semantics as a semantic and textual model for translation quality assessment. The text for this case study is an excerpt under the title “Слово некоего калугера о чьтьи книг” (“The Discourse of a Certain Monk in Reading Scripture”) from the collection “Izbornyk of Sviatoslav of 1076”, and its three translations: two translations into modern Ukrainian language (the complete one by V. Yaremenko, and the partial one by Ye. Karpilovska and L. Tarnovetska) and one translation into English (by W. Veder). The theory of cognitive semantics by R. Langacker focuses mainly on grammar issues and the description of the language via space parameters. Cognitive semantic dimensions for describing imagery lack clarity which is enjoyed by analytical methods in structuralism. However, they perform the main analytical function: they make it possible to show how and why violations and deviations from the original occur in a translated text as well as what their essence and limits are. References Бычков В. 2000 лет христианской культуры sub specie aesthetica : в 2 т. Т. 2 : Славянский мир. Древняя Русь. Россия. Москва; Санкт-Петербург : Университетская книга, 1999. Bychkov, V. (1999). 2000 let khrystyanskoi kultury sub specie aesthetica. T. 2: Slavianskyi myr. Drevniaia Rus. Rossyia. [2000 years of Christian culture sub specie aesthetica. Vol. Slavonic world. Old Rus. Russia]. Moscow; S.-Petersburg: Unyversytetskaya Kniga. Божилов И. Цар Симеон Велики (893–927): Златният век на Средновековна България. София: На отечествения фронт, 1983. Bozhylov, Y. (1983).Tsar Symeon Velyky (893–927): Zlatnyiat vek na Srednovekovna Balgariya. [Czar Simeon the Great (893–927): the golden epoch of the Medieval Bulgaria]. Sofia: Na Otechestvenyia Front. Великий тлумачний словник сучасної української мови / уклад. і гол. ред. В. Т. Бусел. К.; Ірпінь: ВТФ «Перун», 2005. Velykyi tlumachnyi slovnyk suchasnoi ukrainskoi movy. [A great comprehensive dictionary of the contemporary Ukrainian language]. (2005). Busel, V. T. (comp.). Kyiv; Irpin: Perun. ЕСУМ: Етимологічний словник української мови. – К.: Наукова думка, 1982. Etymolohichnyi slovnyk ukrayinskoyi movy. [An etymological dictionary of the Ukrainian language]. (1982). Kyiv: Naukova Doumka. Изборник 1076 года. М.: Наука, 1965. Izbornik 1076 goda. [A synaxarion of 1076]. (1965). Moscow: Nauka. Золоте слово / упорядн. : В. Яременко, О. Сліпушко. Київ: Аконіт, 2002. Zolote slovo. [Golden word] (2002). Yaremenko, V., Slipushko, O. (comp.). Kyiv: Akonit. Каждан А. П. Книга и писатель в Византии. Москва: Наука, 1973. Kazhdan, A. P. (1973). Kniga i pisatel v Vizantii. [Books and writers in Byzantium]. Moscow: Nauka. Київський псалтир : Давида пророка и царя пhснь. Київ, 1397. Зберігається: Российская Национальная библиотека (Санкт-Петербург). Шифр: ОЛДП F 6. Kyivskyi psaltyr: Davyda proroka i tsaria pisn. [The psalm book of Kyiv] (1397). Kyiv. Manuscript. Stored at: Russian National Library (Saint-Petersburg). Code: OLDP F 6. Книга правил святих апостолів, Вселенських і Помісних Соборів і святих Отців. К.: Видання Київської Патріархії Української Православної Церкви Київського Патріархату, 2008. Knyha pravyl sviatykh apostoliv, Vselenskykh i Pomisnykh Soboriv i sviatykh Ottsiv. [A book of rules of Saint Apostles, Ecumenical and Local Councils and Holy Fathers]. (2008). Kyiv: Vydannia Kyivskoyi Patriarkhiyi Ukrayinskoyi Pravoslavnoyi Tserkvy Kyivskoho Patriarkhatu. Малоруско-нїмецкий словар / уложили Є. Желеховский, С. Недїльский. Львів : Т-во ім. Шевченка, 1886. Malorusko-nimetskyi slovar. [A Ukrainian-German dictionary]. (1886). Zhelekhovskyi, Ye., Nedilskyi, S. (comp.). Lviv: Tovarystvo im. Shevchenka. Настольная книга священнослужителя. Т. 4. Москва, 1983. Nastolnaia kniga sviashchennosluzhytelia. T. 4. [A priest’s handbook. Vol. 4]. (1983). Moscow. Пиккио Р.Slavia Orthodoxa: Литература и язык. Москва : Знак, 2003. Piccio, R. (2003). Slavia Orthodoxa: Literatura i yazyk. [Slavia Orthodoxa: Literature and language]. Moskcow: Znak. Православная энциклопедия. Т. 16. Москва : Церк.-науч. центр «Православная энциклопедия», 2007. Pravoslavnaia Entsyklopediia. T. 16. [Orthodox Encyclopedia. Vol. 16]. (2007). Moscow: Church and Scientific Center “Pravoslavnaia Entsyklopediia”. Сивокінь Г.М. Одвічний діалог: (Українська література і її читач від давнини до сьогодні). Київ : Дніпро, 1984. Syvokin, H. M. (1984). Odvichnyi dialoh: (Ukrainska literatura i yiyi chytach vid davnyny do sohodni). [The eternal dialogue: Ukrainian literature and its readership from the old times till nowadays]. Kyiv: Dnipro. Словарь древнерусского языка (XI–XIV вв.) / гл. ред. Р. И. Аванесов. Москва: Рус. яз., 1988. Slovar drevnerusskoho yazyka (XI–XIV vv.). [A dictionary of the Russian language of the 11th –14th centuries]. (1988). Avanesov, R. Y. (ed.-in-chief). Moscow: Russkiy Yazyk. Словарь русского языка ХІ–XVII вв. Москва: Наука, 1975. Slovar Russkogo Yazyka ХІ–XVII vv. [A dictionary of the Russian language of the 11th - 17th centuries]. (1975). Moscow: Nauka. Slovar Staroslavianskogo Yazyka. [A dictionary of the Old Slavonic language]. (2006). Saint-Petersburg. Словарь української мови / упор. з дод. влас. матеріалу Б. Грінченко. Київ, 1907– 1909. Slovar Ukrayinskoyi Movy. [A Dictionary of the Ukrainian language]. (1907–1909). Hrinchenko, B. (comp.) Kyiv. Срезневскій И.И. Матеріалы для словаря древне-русскаго языка по письменнымъ памятникамъ. Санктпетербургъ, 1893–1912. Sreznevskiy, I. I. (1893–1912). Materialy Dlia Slovaria Drevne-russkago Yazyka po PismennymPpamiatnikam. [Materials for the Dictionary of the Old Rus Language as Based on Written Monuments ].Saint-Petersburg. Словник української мови. Київ : Наукова думка, 1970–1980. Slovnyk Ukrayinskoyi Movy. [A Dictionary of the Ukrainian language]. (1970–1980). Kyiv: Naukova Doumka. Словник староукраїнської мови XIV–XV ст. Київ: Наук. думка, 1977–1978. Slovnyk Staroukrayinskoyi Movy XIV–XV st. [A Dictionary of the Ukrainian Language of the 14th –15th centuries]. (1977–1978). Kyiv: Naukova doumka,. Словник української мови XVI – першої половини XVII ст. Львів, 1994. Slovnyk Ukrayinskoyi Movy XVI – Pershoyi Polovyny XVII st. [A Dictionary of the Ukrainian Language of the 16th to the first half of the 17th centuries]. (1994). Lviv. Українська література ХІ–ХVІІІ століть / упоряд. Є. А. Карпіловська, Л. О. Тарновецька. Чернівці : Прут, 1997. Ukrayinska Literatura ХІ–ХVІІІ stolit. [Ukrainian Literature of the 11th –18th Centuries]. (1997).Ye. A. Karpilovska, L. O. Tarnovetska (Eds.). Chernivtsi: Prut. Франко І. Із лектури наших предків ХІ в. // Франко І. Додаткові томи до Зібрання творів у п’ятдесяти томах / І. Франко. Київ : Наук. думка, 2010. Т. 54. С. 911–922. Franko, I. (2010). Iz lektury nashykh predkiv ХІ v. [From the Readings of our Ancestors in the 11th century]. In: Dodatkovi Tomy do Zibrannia Tvoriv u Pyatdesiaty Tomakh . Vol. 54 (pp. 911–922). Kyiv: Naukova doumka. Цейтлин Р.М. Лексика старославянского языка: Опыт анализа мотивированных слов по данным древнеболгарских рукописей Х—ХІ вв. Москва: Наука, 1977. Tseitlin, R. M. (1977). Leksika Staroslavianskogo Yazyka: Opyt Analiza Motivirovannykh Slov po Dannym Drevnebolgarskikh Rukopisei Х—ХІ vv. [Lexis of the Old Slavonic Language: A Case Study of Derived Vocabulary in the Old Bulgarian Manuscripts of the 10th–11th centuries]. Moscow: Nauka. The Compact Edition of the Oxford English Dictionary: Complete Text Reproduced Micrographically. (1971). Oxford: Oxford University Press. The Compact Edition of the Oxford English Dictionary: Complete Text Reproduced Micrographically. (1987). Burchfield, R. W. (ed.). Oxford u.a.: Clarendon Press. The Edificatory Prose of Kievan Rus’ (1994). Veder, W. R. (trans.). Cambridge, MA: Harvard University Press. Henry, M. (1972). Commentary on the Whole Bible: Complete and Unabridged in 2 Volumes. Wilmington, Delaware: Sovereign Grace. Langacker, R. (1988). A View of Linguistic Semantics. In: Topics in Cognitive Linguistics (pp. 49–89). Amsterdam: Benjamins. Langacker, R. W. (1987). Foundations of Cognitive Grammar. Stanford CA: Stanford University Press. New Catholic Encyclopedia. (2002–2003). Detroit: Thomson/Gale. Sophocles, E. A. (1914). Greek Lexicon of the Roman and Byzantine periods: (from B. C. 146 to A.D. 1100). Cambridge : Harvard University Press ; London: Humphrey Milford. Stockwell, P. (2002). Cognitive Poetics: An Introduction. London: Routledge.